Pesan Dakwah Dr. Fahrudin Faiz “Nizami Ganjavi-Layla Majnun” di YouTube MJS Channel - Sri Umyati (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. This research digs deeper into the analysis of text structure, social cognition, and social context in dakwah messages. The method used is critical discourse analysis with a qualitative approach. This research is focused on the meaning behind the story of Layla Majnun. In this video, there are three messages of dakwah: the message of Akidah, namely the command to love Allah; the moral message, namely the way we do good to fellow human beings; and the message of sharia, namely carrying out His commands and avoiding His prohibitions. The results of the study illustrate that, in terms of social cognition, Dr.'s preaching messages. Fahrudin Faiz contains information about divine love that relates to existing social phenomena. In a social context, dakwah messages contain how we can relate well to fellow human beings. But of these three aspects the most dominant found by researchers is in the message of faith. The implication of this research is that researchers who want to research videos in the future must know very well the theory used, and especially for the Department of Islamic Communication and Broadcasting to teach special courses on semiotics, because researchers see for themselves that many students from the Department of Islamic Communication and Broadcasting are interested in using this theory, but this theory has never been taught specifically. Abstrak. Penelitian ini menggali lebih dalam bagaimana analisis struktur teks, kognisi sosial dan konteks sosial dalam pesan dakwah Dr. Fahrudin Faiz. Metode yang digunakan adalah Analisis wacana kritis dengan pendekatan kualitatif. Penelitian ini difokuskan pada makna dibalik cerita Layla Majnun. Dalam video ini memiliki tiga pesan dakwah, pesan akidah yaitu perintah untuk mencintai Allah, pesan akhlak yaitu dengan cara kita berbuat baik kepada sesama manusia, pesan syariah yaitu menjalankan perintah-Nya dan menjauhi larangan-Nya. Hasil penelitian menggambarkan bahwa secara kognisi sosial, pesan dakwah Dr. Fahrudin Faiz berisikan tentang cinta ketuhanan yang dihubungkan dengan fenomena sosial yang ada. Dalam konteks sosial, pesan dakwah berisikan tentang bagaimana kita bisa berhubungan dengan baik sesama manusia. Namun dari ketiga aspek tersebut yang paling dominan yang ditemukan oleh peneliti terdapat pada pesan akidah. Implikasi dari penelitian ini adalah peneliti yang ingin meneliti video selanjutnya harus mengetahui betul teori yang digunakan, dan terkhusus untuk Jurusan Komunikasi dan Penyiaran Islam agar sekiranya mengajarkan mata kuliah khusus tentang semiotika, karena peneliti melihat sendiri banyak mahasiswa dari Jurusan Komunikasi dan Penyiaran Islam yang tertarik untuk menggunakan teori ini akan tetapi teori ini belum pernah diajarkan secara khusus.